2017
DOI: 10.1038/srep40142
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification of pericardial patches for sustained rapamycin delivery inhibits venous neointimal hyperplasia

Abstract: Prosthetic grafts and patches are commonly used in cardiovascular surgery, however neointimal hyperplasia remains a significant concern, especially under low flow conditions. We hypothesized that delivery of rapamycin from nanoparticles (NP) covalently attached to patches allows sustained site-specific delivery of therapeutic agents targeted to inhibit localized neointimal hyperplasia. NP were covalently linked to pericardial patches using EDC/NHS chemistry and could deliver at least 360 ng rapamycin per patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 35 publications
(46 reference statements)
4
36
0
Order By: Relevance
“…There was also a significant thinner adventitial layer of the IP injection and coating patches (Figure 3a,c). These results are similar to our previous data showing that rapamycin decreases neointimal hyperplasia that forms on patches 17 …”
Section: Resultssupporting
confidence: 93%
“…There was also a significant thinner adventitial layer of the IP injection and coating patches (Figure 3a,c). These results are similar to our previous data showing that rapamycin decreases neointimal hyperplasia that forms on patches 17 …”
Section: Resultssupporting
confidence: 93%
“…We previously showed that nanoparticles covalently bonded to pericardial patches can deliver therapeutic agents to the adjacent vena cava. 18 We confirmed that this strategy could similarly deliver drugs to the aorta after aortic patch angioplasty. Nanoparticles containing rhodamine were bonded to patches and used for aortic patch angioplasty; as expected, rhodamine was delivered to the aortic wall, with increased delivery over 24 hours (Supplementary figure 4).…”
Section: Resultssupporting
confidence: 68%
“…Combined with nanoparticles engineered to exhibit slow drug release kinetics, the pericardium can function as a sustained release drug-eluting depot for prolonged drug delivery to the heart. Recently, Hualong and coworkers demonstrated neointimal hyperplasia inhibition through sustained rapamycin delivery from a pericardial patch [51], successfully limiting smooth muscle cell migration and hyperplasia.…”
Section: Discussionmentioning
confidence: 99%